From Interdisiplinary Interactions Toward Interdisciplinary Knowledge - Yanitsky, Oleg (Advances in Social Sciences Research Journal, 2020)
The article presents a set of arguments on favor of an interdisciplinary approach to any events and transformations of the global SBT-system. Drawing on my previous social experience, the analysis of relevant scientific literature and my own studies on the emergence and development of current pandemics I came to the following conclusions. First, every social or natural action has an interdisciplinary character. Second, the regularities of global SBT-structure development and its feedbacks in relation to global economic and social life are still ill studied. Third, the key moment of any natural and social transformation and the interdisciplinary collaboration are the metabolic processes between qualitatively different essences. Four, the above changes points to the fact that the XX century and further has transformed a scientific thought and knowledge into the planetary phenomena. Five, it’s reflects that under current conditions all are interrelated with all. Six, the interdisciplinary approach to an SBT-system of any scale and mode of development has become absolutely necessary. Seven, the emergence and quick spread the pandemics across the world I call as the global critical situation, and it means that the global SBT-system has become over-integrated.